Inhibitory test of Dayak onion extract (eleutherine palmifolia) (L) merragainst gram negative and gram positive bacteria - Ni Made Susilawati; Meliance Bria; Neiny P Foekh (Science Midwifery, 2022)
Dayak onion tubers contain chemical compounds such as alkaloids, glycosides, flavonoids, phenolics, steroids and tannins which are potential sources to be developed as medicinal plants. Dayak onions grown in different soil topography produce different secondary metabolite content even though they are from the same species. The purpose of this study was to determine the potential of Dayak onion (Eleutherine palmifolia) (L) Merr extract to have inhibitory potential and the amount of inhibition on the growth of Gram-positive and Gram-negative bacteria. This study is a laboratory experiment using a post test with a group design with 10 treatment groups, namely 1% Dayak onion extract, up to 10% with 5% DMSO solvent, control using 0.85% NaCl tested on Gram positive and Gram negative bacteria. Dayak onion extract (Eleutherine palmifolia) (L) Merr which was tested on the Gram negative bacteria group Escherichia coli, Klebsiella pneumoniae and Pseudomonas aeruginosa gave weak inhibitory results, while the Dayak onion extract (Eleutherine palmifolia) (L) Merr which was tested on the bacterial group Gram positive Stapylococcus aureus, Staphylococcus epidemicdis, Staphylococcus saprophyticus give strong inhibitory results.